Diagnosis and therapy of polycythemia vera - Lengfelder, Eva; Merx, Kirsten; Hehlmann, Rüdiger (Seminars in thrombosis and hemostasis, 2006)
Polycythemia vera (PV) is a hematopoietic stem cell disorder characterized by a predominant proliferation of the erythroid cell line. The diagnosis is commonly based on the WHO criteria. The acquired V617F mutation in the tyrosine kinase gene JAK2 represents a new molecular marker proving clonality in PV and other chronic myeloproliferative disorders. Phlebotomy is still the treatment of choice to reduce the red cell mass. Low-dose acetylsalicylic acid is successful in the primary prophylaxis of vascular complications. However, the majority of patients require myelosuppressive therapy during the course of their disease due to progressive myeloproliferation. Hydroxyurea still plays a role in patients of all age groups. Interferon α represents an alternative, particularly for younger patients. Apart from sporadic cases of bone marrow transplantation, there is no known curative treatment in PV. To date, the diagnosis of PV was based mainly on clinical criteria. The identification of the JAK2 mutation enables new approaches to the diagnosis, classification, and treatment of PV and of the other myeloproliferative disorders.
Gesehen am 10.05.2022